Performance comparison of a standing-wave thermoacoustic engine with different resonator shapes with air working gas - Zahra Bouramdane; Abdellah Bah (International Journal of Air-Conditioning and Refrigeration, 2024)
Abstract The resonator is one of the key components of thermoacoustic machines and the choice of its geometry is of course of crucial importance, as it determines the way the machine operates. The resonator must be designed so that the quality factor of the resonance is as high as possible and must satisfy the technological production constraints related to the high pressurization of the working fluid and the presence of temperature non-uniformities. The shape of the resonator can be modified to reduce certain loss phenomena, particularly on the walls, and to limit the formation of harmonics in the high-level acoustic field. In this work, an acoustic power losses analysis and a numerical study of a standing-wave TAE with air working gas, considering changes in resonator shape, are performed to investigate the effect of resonator geometry on the thermoacoustic energy conversion. The acoustic power dissipation in the resonator is analyzed based on the simplified thermoacoustic theory and the numerical study is conducted based on a 2D numerical model based on a CFD analysis. Results show that the shape of the resonator significantly affects the frequency, the temperature along the stack, and the acoustic pressure produced on the TAE. In addition, it is shown that the resonator composed of two different diameters showed its ability to produce a high acoustic pressure amplitude (20.5% than the iso-diameter resonator) and minimize the viscous and thermal losses.